Use of hardening soil model for excavation in residual soil - Sherly (2018)
The scarcity of land and the growing population have led the development of underground space and transportation system to meet people needs. Nowadays, many buildings require underground spaces for carparks and underground spaces are required for MRT stations or tunnels. Thus, braced excavation is required for deep excavation projects to ensure overall system stability. This project studies the braced excavation performance for residual soils. The parameters studied include dewatering level, soil strength, and residual soil thickness. The dewatering method was also studied. The braced excavation performance focuses on three aspects; maximum lateral wall deflection, maximum soil settlement, and maximum strut forces. There are 13 cases analyzed using the finite element software PLAXIS 2D. The results indicate that lowering the dewatering level at the active side was not significant for the braced excavation system performance. As dewatering level decreased, the maximum soil settlement slightly increased because of the change in effective stress of soil. In addition, the maximum wall deflection and strut forces decreased slightly as the active force towards the diaphragm wall decreased. The soil analysis also shows the decrease in wall deflection and soil settlement as the soil strength and stiffness are increased. The decrease is more gradual when the SPT N value of the residual soil is greater than 15. For the analysis of the residual soil thickness, it is shown that the increase in residual soil thickness caused the increase in maximum wall deflection, maximum soil settlement, and maximum strut forces as well.